Phenolics in food and nutraceuticals - Shahidi, Fereidoon (CRC Press LLC, 2011)
Phenolics in Food and Nutraceuticals is the first single-source compendium of essential information concerning food phenolics. This unique book reports the classification and nomenclature of phenolics, their occurrence in food and nutraceuticals, chemistry and applications, and nutritional and health effects. In addition, it describes antioxidant activity of phenolics in food and nutraceuticals as well as methods for analysis and quantification. Each chapter concludes with an extensive bibliography for further reading. Food scientists, nutritionists, chemists, biochemists, and health professionals will find this book valuable.